Electrocatalytic Activity for Oxygen Reduction Reaction of Au Core/Pt Shell Nanoparticle-Loaded Carbon Black Catalyst with Different Core Sizes. (10th October 2015) - Higuchi, Eiji; Okada, Kohei; Chiku, Masanobu; Inoue, Hiroshi
Highlights: Au NPs was prepared by bubbling CO through AuCl4 − aqueous solution containing glutathione. The Au NP particle size remained 2.5 ± 0.5nm during electrochemical treatment. SSAPt did not decrease during CV in O2 suggesting PtAu did not form. MAPt for Pt/AuG /CB-ET was 6.6 times higher than that for commercial Pt/CB. Reducing the core size of Au NPs increased MAPt . Abstract: Au core/Pt shell nanoparticle-loaded carbon black catalysts were prepared by forming a Pt monolayer on newly prepared Au nanoparticles and their electrocatalytic activities for the oxygen reduction reaction (ORR) were evaluated by the rotating disk electrode method. The Au nanoparticles were prepared by bubbling CO as a reducing agent in KAuCl4 aqueous solutions containing glutathione (GSH) as a stabilizer, and GSH on the resultant Au nanoparticles was removed by electrochemical oxidation. Underpotential deposition of Cu on the electrochemically treated Au nanoparticles (AuG -ET) and subsequent galvanic displacement of Cu with Pt led to the production of Au core/Pt shell nanoparticle-loaded carbon black (AuG -ET@Pt). In the X-ray photoelectron spectra, the S 0 peak of AuG -ET completely disappeared, while the Au 0 peaks returned to their intrinsic positions. From transmission electron microscopy images, particle size of Au on AuG -ET was 2.5 ± 0.5 nm. These results indicate that GSH was completely removed from the Au surface without increasing the size. The Pt coverage of AuG -ET@Pt was 0.95. The electrocatalytic activity per unit mass of Pt (MAPt ) at 0.9 V vs RHE for the AuG -ET@Pt was 1.3 and 6.6 times higher than that for our previous Au@Pt of 2.8 ± 0.5 nm in size and commercial Pt/carbon black, respectively. Reducing the size of the Au nanoparticles can increase MAPt . After durability test, the particle size and standard deviation of AuG -ET@Pt were 3.9 ± 0.9 nm, which were larger than the initial values (3.0 ± 0.5 nm), leading to the decrease in specific surface area of Pt.